Konseptual Desain Pesawat UAV Meniru Cessna 172 Dengan Konfigurasi Sayap Morphing Untuk Misi Trainer - Mizan Fadhilah; Haqqah Risath Mas Intan (Journal of Applied Mechanical Technology, 2022)
The development of UAVs/drones in Indonesia is growing rapidly, as evidenced by many domestically made UAVs/drones, because indeed the existence of these drones can assist human tasks in certain fields, therefore researchers are interested in designing a UAV concept for trainer mission purposes with a morphing wing configuration that will be reserved for novice pilots as a condition for obtaining drone pilot certification. By using calculations using the Anderson method, the output of the calculation will be used as a reference in the preparation and manufacturing of the conceptual design of the aircraft to be made. The initial estimated weight of the Cessna 172 UAV aircraft with a morphing wing configuration for trainer mission purposes is 5.375433 lb with a fuselage length of 5.15304 ft, and a wingspan of 5.266345 ft which is positioned above the fuselage, and is powered by 1 engine motor. brushless of 0.129642 hp